HATE SPEECH ON RAGIL MAHARDIKA’S INSTAGRAM - Emeliya Damanik; Jenita Anjani br Sembiring (Yavana Bhasha : Journal of English Language Education, 2023)
Individuals who respect normative ideals should communicate carefully, particularly on social media. Instagram, for example, is a popular social media platform that is now used by active users. The hate speech on Ragil Mahardika's social media accounts is a reflection of the behavior of internet users who purposefully post comments and opinions about Ragil Mahardika's life. This research will also look into the many sorts of hate speech. Descriptive qualitative research with supporting theory was employed as the research approach. According to Waldron (2010), hate speech is defined as a word that tries to hate, violate, or discriminate against groups based on race, color, religion, or national origin by offending, threatening, or insulting them. Related to the finding, there are three types of hate speech uttered by netizens on Ragil's Instagram; words, phrases and sentences. The three types of hate speech tend to dysphemia. Because of the expression contains dysphemia, it can be categorized as hate speech.